Control interno y su relación con el cumplimiento de metas en la municipalidad distrital de Yarinacocha, 2020 - Rios García, Fernando Daniel (2021)
The main objective of this study was to establish the relationship between internal control and the fulfillment of goals in the district Municipality of Yarinacocha, 2020; being a study of a non-experimental type and descriptive-correlational design, taking into account a population and sample of 24 collaborators from the aforementioned institution, for which the survey technique has been used and the questionnaire created from the dimensions and indicators of each variable; procedure and data analysis that led to conclude the following: It was determined that there is a significant relationship between internal control and the fulfillment of goals, a relationship established by the significance of 0.000 and a correlation coefficient of 0.873 which is considerable positive. Likewise, it was determined that there is a significant relationship between internal control and the fulfillment of specific individual goals, a relationship established by the significance of 0.000 and a correlation coefficient of 0.835, which is considerable positive. In addition, it was determined that there is a significant relationship between internal control and the fulfillment of operational goals, a relationship established by the significance of 0.000 and a correlation coefficient of 0.882, which is considerable positive. Finally, it was determined that there is a significant relationship between internal control and the fulfillment of official goals, a relationship established by the significance of 0.000 and a correlation coefficient of 0.894, which is considerably positive.